Rotator Cerclage Technique for Partial Rotator Cuff Ruptures - Murat Bozkurt, M.D.; Ahmet Firat, M.D.; Safa Gursoy, M.D.; Mustafa Akkaya, M.D. (Arthroscopy Techniques, 2015)
The frequency of partial rotator cuff tears is gradually increasing because of the advancements in imaging methods and arthroscopy techniques. One of the repair techniques is repair of the partial rotator cuff tear by conversion to a full-thickness tear. Another technique, the transtendon technique, has some practical challenges and risks. We attempted to develop a practical and easy technique with low morbidity to repair partial tears called the rotator cerclage technique.